2009
DOI: 10.1002/jpln.200800072
|View full text |Cite
|
Sign up to set email alerts
|

Acidity, nutrient stocks, and organic‐matter content in soils of a temperate deciduous forest with different abundance of European beech (Fagus sylvatica L.)

Abstract: The production and composition of leaf litter, soil acidity, exchangeable nutrients, and the amount and distribution of soil organic matter were analyzed in a broad‐leaved mixed forest on loess over limestone in Central Germany. The study aimed at determining the current variability of surface‐soil acidification and nutrient status, and at identifying and evaluating the main factors that contributed to the variability of these soil properties along a gradient of decreasing predominance of European beech (Fagus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
163
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 168 publications
(192 citation statements)
references
References 33 publications
25
163
3
1
Order By: Relevance
“…This ratio from our study confirmed the enrichment of T 4 treatment in phosphorus. These results are similar to those obtained by Güsewell and Verhoeven (2006) and Guckland et al (2009), where N:P ratio was 16:1 during the decomposition of leaves and 11:1 in the soil, respectively. Panicum maximum at 3 week age contains 32.3% calcium, 46.6% phosphorus, and 71% of magnesium (Oyenuga 1960).…”
Section: Discussion Diet and Manure's Nutrient Contentsupporting
confidence: 91%
“…This ratio from our study confirmed the enrichment of T 4 treatment in phosphorus. These results are similar to those obtained by Güsewell and Verhoeven (2006) and Guckland et al (2009), where N:P ratio was 16:1 during the decomposition of leaves and 11:1 in the soil, respectively. Panicum maximum at 3 week age contains 32.3% calcium, 46.6% phosphorus, and 71% of magnesium (Oyenuga 1960).…”
Section: Discussion Diet and Manure's Nutrient Contentsupporting
confidence: 91%
“…An exception was those in the 10-20 and 20-30 cm soil layers of the 10-yearold stand, which showed slight differences. Many researchers have demonstrated the species diversity or species identity effects on soil OC and N accumulation in forests and revealed that species diversity and/or abundance of dominant tree species exerts effects on OC and N stocks through carbon input by litter and fine roots (Berger et al, 2002;Guckland et al, 2009;Wang et al, 2013;Dawud et al, 2016). In a previous study at this site, the annual litterfall was also the highest in the mixed Pinus-Cinnamomum stand followed by Pinus; Cinnamomum was the lowest (Xu et al, 2013).…”
Section: Soil Organic Carbon and Nitrogen Stocksmentioning
confidence: 71%
“…Recent studies of soil properties in mixtures or along species diversity gradients have also tended to mix tree species with a relatively wide range in tree species traits such as litter nutrient and lignin concentration [24,45]. It is therefore interesting to test whether beech and Douglas-fir, given their relatively similar footprints on the soil in monocultures, would lead to synergistic (non-additive) effects on key soil properties in mixtures.…”
Section: Effects Of Beech and Douglas-fir Mixturesmentioning
confidence: 99%